Micronuclear induction in response to methylmercury exposure in the air breathing fish Anabas testudineus (Bloch, 1792) - Swetha, S.; Pramod Kiran, R. B. (Indian Journal of Fisheries, 2021)
Natural and man-made chemicals like mercury have Â been implicated as malefactors in various ailments and are even considered genotoxic since long. Methylmercury (MeHg), the organic compound of mercury, -is known to cause genetic variations in many organisms spanning all spheres of life. The present study was conducted to identify the formation of nuclear anomalies on exposure to MeHg in the freshwater air breathing fish Anabas testudineus (Bloch, 1792) using micronucleus (MN) assay.Â Acute toxicity (LC50) of MeHg was calculated to be 438 Î¼g Â l-1 using probit analysis. The fishes were exposed to 1/5th concentration of LC50 (87.6 Î¼g l-1 ) and blood samples collected on days 0, 4 and 15 were analysed for induction of MN. The percentage of MN formation per 1000 cells was the highest (19.35) in the juveniles on day 15. It is concluded that A. testudineus is sensitive to MeHg and micronuclear assay of the species can be used as a potential biomarker in the event of contamination in aquatic ecosystems. Keywords: Anabas, MeHg, Micronucleus, Sublethal